Research Progress of Catalysts for Hydrogen Production by Electrolysis of Water - Huang Ruiyang (MATEC Web of Conferences, 2025)
Hydrogen energy is the main energy carrier to promote energy transformation in today's society, and electrolytic water hydrogen production technology is relatively mature at present, and has the characteristics of environmental protection, energy saving and high efficiency, making it the main way to produce hydrogen in life and industrial production. The catalyst is the key factor to improve the efficiency of electrolytic water and make it more widely used in industrial production and daily life. In this paper, the principle of water electrolysis and the calculation of Gibbs free energy in thermodynamics are summarized, so as to obtain the theoretical potential and its application and hindrance in practice. The mechanism of the catalyst is introduced by introducing the bonding orbital theory. And focuses on the precious metal catalyst, transition metal catalyst, non-metal catalyst these three kinds of water electrolysis catalyst research, characteristics and its application. The future research will focus on making the working condition more stable and optimizing the theoretical and experimental closed loop through the precise control of electronic structure and the design of multi-scale structure.